Impact of Cannabis Use during Stabilization on Methadone Maintenance Treatment. (25th June 2013) - Scavone, Jillian L.; Sterling, Robert C.; Weinstein, Stephen P.; Van Bockstaele, Elisabeth J.
<x xml:space="preserve">Abstract</x> Background and Objectives Illicit drug use, particularly of cannabis, is common among opiate‐dependent individuals and has the potential to impact treatment in a negative manner. Methods To examine this, patterns of cannabis use prior to and during methadone maintenance treatment (MMT) were examined to assess possible cannabis‐related effects on MMT, particularly during methadone stabilization. Retrospective chart analysis was used to examine outpatient records of patients undergoing MMT (n = 91), focusing specifically on past and present cannabis use and its association with opiate abstinence, methadone dose stabilization, and treatment compliance. Results Objective rates of cannabis use were high during methadone induction, dropping significantly following dose stabilization. History of cannabis use correlated with cannabis use during MMT but did not negatively impact the methadone induction process. Pilot data also suggested that objective ratings of opiate withdrawal decrease in MMT patients using cannabis during stabilization. Conclusions and Scientific Significance The present findings may point to novel interventions to be employed during treatment for opiate dependence that specifically target cannabinoid–opioid system interactions. (Am J Addict 2013;22:344–351)